Transcallosal Mechanism of Mirror Movements - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The mechanism of mirror movements in 11 normal adults and 39 children (aged 4-11 years) was studied in the Department of Physiology, University College London, UK.